THE ANALYSIS OF INFORMATION CHANGE STRATEGY IN FINDING CULTURAL EQUIVALENCE IN TRAVEL WRITING - Arsiwela, Arsiwela; Topan, Tegar Arif (Journal of Language and Literature, 2023)
The function of translation is to transfer message from source language text into target language text. However, in translating, the translator will face some problems, for example is the translation of cultural words. Strictly speaking, the translator has difficulty in finding an equivalent of cultural words, since there is no direct and right equivalent which is used to carry the meaning of source language in word or phrase to target language. This research invertigates how cultural words in travel writing are translated. The method applied in this study is qualitative descriptive method. The number of the data were taken from Titik Nol novel written by Agustinus Wibowo and its translation Ground Zero into English by MT (Editor: John Michaelson). The theory used to analyze the research data is Chesterman’s theory, specifically information change on the pragmatic strategies. From the findings of the research, the researcher concludes two categories of information change strategies. Out of the 11 data which are analyzed in this research, there are 10 data that used new addition strategy, and 1 data used omission strategy.